Strain-level genomic analysis of serotype, genotype and virulence gene composition of group B streptococcus - Zhen Zeng; Meng Li; Simin Zhu; Ke Zhang; Yifan Wu; Minzi Zheng; Yang Cao; Zhenyu Huang; Qinping Liao; Lei Zhang; Lei Zhang (Frontiers in Cellular and Infection Microbiology)
IntroductionGBS (group B streptococcus) is an opportunistic pathogen that can colonize healthy individuals but presents significant challenges in clinical obstetrics and gynecology, as it can cause miscarriage, preterm birth, and invasive infections in newborns. To develop specific and personalized preventative strategies, a better understanding of the epidemiological characteristics and pathogenic features of GBS is essential.MethodsWe conducted a comprehensive strain-level genomic analysis of GBS, examining serotype and genotype distributions, as well as the composition and correlations of virulence genes using the blastn-short mode of the BLAST program(v2.10.0+), mlstsoftware (https://github.com/tseemann/mlst), Snippy (v4.6.0), FastTree (v2.1.11) and iTOL. The coding sequence region of virulence factors was annotated by Prodigal (v2.6.3) and Glimmer(v3.02b). We further identified host protein interacting with Srr2 by mass spectrometry analysis.ResultsWhile certain genotypes showed strong serotype consistency, there was no significant association between overall serotypes and genotypes. However, the composition of virulence genes was more closely related to the phylogeny of GBS, among which simultaneous presence of Srr2 and HygA exhibit significant association with hypervirulence. Tubulin emerged as the most distinct and abundant hit. The specific interaction of Tubulin with Srr2-BR, rather than Srr1-BR, was further confirmed by immunoblotting.DiscussionConsidering the impact of cytoskeleton rearrangement on GBS pathogenesis, this observation offers a plausible explanation for the hypervirulence triggered by Srr2. Collectively, our findings indicate that in the future clinical practice, virulence gene detection should be given more attention to achieve precise GBS surveillance and disease prevention.